Attracting Flows by Attracting Big Clients - COHEN, LAUREN; SCHMIDT, BRENO (Journal of Finance, 2009)
We explore a new channel for attracting inflows using a unique data set of corporate 401(k) retirement plans and their mutual fund family trustees. Families secure substantial inflows by being named trustee. We find that family trustees significantly overweight, and are reluctant to sell, their 401(k) client firm's stock. Trustee overweighting is more pronounced when the relationship is more valuable to the trustee family, and is concentrated in those funds receiving the greatest benefit from the inflows. We quantify this flow benefit and find that inclusion in the 401(k) plan has an economically and statistically large, positive effect on inflows.